PENGARUH BIAYA PERJALANAN, UMUR, JARAK DAN PENDAPATAN TERHADAP KEPUTUSAN PENGUNJUNG WISATA WADUK JEULIKAT KOTA LHOKSEUMAWE - Hijri Juliansyah; Masniar Masniar; Tarmizi Abbas (Jurnal Ekonomi Regional Unimal, 2021)
This study aims to analyze the effect of Travel Cost, Age, Distance and income on the decision of visitors of Waduk Jeulikat, Lhokseumawe City. This study uses primary data obtained by distributing questionnaires to 67 respondents who are visitors of Waduk Jeulikat. The sampling technique used is Random Sampling technique. The data analysis method used is multiple linear regression and classic assumption tests in the form of normality test, multicollinearity test, and heteroscedasticity test. The results of the study partially find that travel cost has a negative and significant effect on the decision of visitors of Waduk Jeulikat, Lhokseumawe City, age does not have a positive and significant effect on decision of visitors of Waduk Jeulikat, Lhokseumawe City, distance has a positive and significant effect on the decision of visitors of  Waduk Jeulikat, Lhokseumawe City, and income has a positive and significant effect on the decision of visitors of Waduk Jeulikat, Lhokseumawe City. Simultaneously, travel cost, age, distance, and income have a positive and significant effect on the decision of visitors to Waduk Jeulikat, Lhokseumawe City.